Search for γ H production and constraints on the Yukawa couplings of light quarks to the Higgs boson - Chekhovsky,V; Hayrapetyan,A; Makarenko,V; Tumasyan,A; Adam,W; Andrejkovic,JW; Benato,L; Bergauer,T; Chatterjee,S; Damanakis,K; Dragicevic,M; Hussain,PS; et al. (Physical Review D, 2025)
A search for <a:math xmlns:a="http://www.w3.org/1998/Math/MathML" display="inline"> <a:mi>γ</a:mi> <a:mi>H</a:mi> </a:math> production is performed with data from the CMS experiment at the LHC corresponding to an integrated luminosity of <c:math xmlns:c="http://www.w3.org/1998/Math/MathML" display="inline"> <c:mn>138</c:mn> <c:mtext> </c:mtext> <c:mtext> </c:mtext> <c:msup> <c:mi>fb</c:mi> <c:mrow> <c:mo>−</c:mo> <c:mn>1</c:mn> </c:mrow> </c:msup> </c:math> at a proton-proton center-of-mass collision energy of <e:math xmlns:e="http://www.w3.org/1998/Math/MathML" display="inline"> <e:mrow> <e:mn>13</e:mn> <e:mtext> </e:mtext> <e:mtext> </e:mtext> <e:mi>TeV</e:mi> </e:mrow> </e:math> . The analysis focuses on the topology of a boosted Higgs boson recoiling against a high-energy photon. The final states of <g:math xmlns:g="http://www.w3.org/1998/Math/MathML" display="inline"> <g:mi>H</g:mi> <g:mo stretchy="false">→</g:mo>